IL-6 is an antiinflammatory cytokine required for controlling local or systemic acute inflammatory responses. - Xing, Z (1998)
IL-6 is induced often together with the proinflammatory cytokines TNFalpha and IL-1 in many alarm conditions, and circulating IL-6 plays an important role in the induction of acute phase reactions. However, whether this endogenous IL-6 plays any additional pro- or antiinflammatory roles in local or systemic responses remains unclear. In this study, the role of IL-6 in acute inflammatory responses was investigated in animal models of endotoxic lung or endotoxemia by using IL-6+/+ and IL-6-/- mice. Aerosol exposure of endotoxin induced increased IL-6 and proinflammatory cytokines TNFalpha and MIP-2 and a neutrophilic response in the lung of IL-6+/+ mice. However, the levels of TNFalpha and MIP-2 and neutrophilia were significantly higher in the lung of IL-6-/- mice. The rate of neutrophil apoptosis in these mice was similar to that in IL-6+/+ mice. A low constitutive level of antiinflammatory cytokine IL-10 was not enhanced by endotoxin and remained similar in the lung in both IL-6+/+ and IL-6-/- mice. Systemically, intraperitoneal delivery of endotoxin resulted in much more pronounced circulating levels of TNFalpha, MIP-2, GM-CSF, and IFNgamma in IL-6-/- mice than in IL-6+/+ mice, and administration of recombinant IL-6 to IL-6-/- mice abolished these differences. In contrast, circulating IL-10 levels were induced to a similar degree in both IL-6+/+ and IL-6-/- mice. Thus, our studies reveal that endogenous IL-6 plays a crucial antiinflammatory role in both local and systemic acute inflammatory responses by controlling the level of proinflammatory, but not antiinflammatory, cytokines, and that these antiinflammatory activities by IL-6 cannot be compensated for by IL-10 or other IL-6 family members.